Simulating infertile acid soils with nutrient solutions: The effects on Brachiaria species - Wenzl, Peter; Mancilla, LI; Mayer, Jorge Edgard; Albert, R.; Rao, Idupulapati M. (2003)
Aluminum toxicity limits plant growth in acid soils. Because of their advanced state of weathering, acid soils of the tropics also tend to be deficient in nutrients. A realistic assessment of plant adaptation to these soils would therefore require Al-toxic conditions under which growth is simultaneously limited by nutrient deficiency. We developed and tested a nutrient solution for this purpose. We analyzed soil solutions of two Oxisols from the Colombian savannas. Nutrient concentrations were extremely low (ionic strength <1.7 mM). Nitrification during incubation of soil samples acidified soil solutions, resulting in a release of cations from the exchange phase, an increase in the activity of Al3+, and a decrease in that of H2PO-4. Predicted ion activities were taken as guidelines for designing a nutrient solution that simulates these soil solutions. Growth of well-adapted signalgrass (Brachiaria decumbens cv. Basilisk) and less-adapted ruzigrass (Brachiaria ruziziensis cv. Common) in this solution mirrored the interspecific difference in forage yield that had previously been observed in a field close to where one of the soils originated. This suggests that the designed solution may be a realistic approximation to chemical soil properties that limit forage productivity. The different growth response of the two grasses was apparently due to increased Al sensitivity of less-adapted ruzigrass under low nutrient supply; neither Al toxicity nor nutrient deficiency alone resulted in a comparable growth difference between the grasses. These data highlight the importance of taking into account interactions among stress factors that occur in parallel in infertile acid soils.